DISTANCE EDUCATION IN RUSSIAN LANGUAGE TEACHING (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The article discusses issues reflecting the content and organization of the educational process of distance learning "Russian language", as well as the features of choosing distance learning.